Crossing the Pacific: Genomics Reveals the Presence of Japanese Sardine ( Sardinops melanosticta ) in the California Current Large Marine Ecosystem - Gary C. Longo; Jeremiah J. Minich; Nicholas Allsing; Kelsey James; Ella S. Adams‐Herrmann; Wes Larson; Nolan Hartwick; Tiffany Duong; Barbara Muhling; Todd P. Michael; Matthew T. Craig (Molecular Ecology, 2024)
Recent increases in frequency and intensity of warm water anomalies and marine heatwaves have led to shifts in species ranges and assemblages. Genomic tools can be instrumental in detecting such shifts. In the early stages of a project assessing population genetic structure in Pacific Sardine ( Sardinops sagax ), we detected the presence of Japanese Sardine ( Sardinops melanosticta ) along the west coast of North America for the first time. We assembled a high quality, chromosome‐scale reference genome of the Pacific Sardine and generated low coverage, whole genome sequence (lcWGS) data for 345 sardine collected in the California Current Large Marine Ecosystem (CCLME) in 2021 and 2022. Fifty individuals sampled in 2022 were identified as Japanese Sardine based on strong differentiation observed in lcWGS SNP and full mitogenome data. Although we detected a single case of mitochondrial introgression, we did not observe evidence for recent hybridization events. These findings change our understanding of Sardinops spp. distribution and dispersal in the Pacific and highlight the importance of long‐term monitoring programs.

Asymmetric interference competition and niche partitioning between native and invasive Anolis lizards - Katherine A. Culbertson; Nicholas C. Herrmann (Oecologia, 2019)

Feedbacks underlie the resilience of salt marshes and rapid reversal of consumer‐driven die‐off - Andrew H. Altieri; Mark D. Bertness; Tyler C. Coverdale; Eric E. Axelman; Nicholas C. Herrmann; P. Lauren Szathmary (Ecology, 2013)
Understanding ecosystem resilience to human impacts is critical for conservation and restoration. The large‐scale die‐off of New England salt marshes was triggered by overfishing and resulted from decades of runaway crab grazing. In 2009, however, cordgrass began to recover, decreasing die‐off ∼40% by 2010. We used surveys and experiments to test whether plant–substrate feedbacks underlie marsh resilience. Initially, grazer‐generated die‐off swept through the cordgrass, creating exposed, stressful peat banks that inhibited plant growth. This desertification cycle broke when banks eroded and peat transitioned into mud with fewer herbivores, less grazing, and lower physical stress. Cordgrass reestablished in these areas through a feedback where it engineered a recovery zone by further ameliorating physical stresses and facilitating additional revegetation. Our results reveal that feedbacks can play a critical role in rapid, reversible ecosystem shifts associated with human impacts, and that the interplay of facilitative and consumer interactions should be incorporated into resilience theory.

A trophic cascade triggers collapse of a salt‐marsh ecosystem with intensive recreational fishing - Andrew H. Altieri; Mark D. Bertness; Tyler C. Coverdale; Nicholas C. Herrmann; Christine Angelini (Ecology, 2012)
Overexploitation of predators has been linked to the collapse of a growing number of shallow‐water marine ecosystems. However, salt‐marsh ecosystems are often viewed and managed as systems controlled by physical processes, despite recent evidence for herbivore‐driven die‐off of marsh vegetation. Here we use field observations, experiments, and historical records at 14 sites to examine whether the recently reported die‐off of northwestern Atlantic salt marshes is associated with the cascading effects of predator dynamics and intensive recreational fishing activity. We found that the localized depletion of top predators at sites accessible to recreational anglers has triggered the proliferation of herbivorous crabs, which in turn results in runaway consumption of marsh vegetation. This suggests that overfishing may be a general mechanism underlying the consumer‐driven die‐off of salt marshes spreading throughout the western Atlantic. Our findings support the emerging realization that consumers play a dominant role in regulating marine plant communities and can lead to ecosystem collapse when their impacts are amplified by human activities, including recreational fishing.